PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PICTURE AND PICTURE UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS V MI IBTIDAUL HUDA TELUK PAPAL KECAMATAN BANTAN - Suhudi, Suhudi; Noviana, Eddy; Syahrilfuddin, Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Indonesian low learning outcomes also occurred in MI Ibtidaul Huda District Bantan. Based on the observation and documentation with Ruzita mother, as a fifth grade teacher Huda MI Ibtidaul District Bantan, in general, very low student learning outcomes. low yields Indonesian language learning students with an average grade 59.00, while the value of minimum completeness criteria (KKM) Bahasa Indonesia is among the 65 students who totaled 22 students were only 7 people who reach KKM. Learning Outcomes Indonesian students was 59.00. After UH1, the average value of students increased to 68.86 with the percentage increase of 9.86%. Furthermore done UH2, the average value of students increased to 80.32 with the percentage increase of 21.32%. teacher activity on cooperative learning model Picture and Picture mode. in the first cycle 1 meeting obtained a score of 18 with a percentage of 56.25% with enough category. At the second meeting of the first cycle, the acquisition of teacher activity observation score of 23 with a percentage of 71.87% in both categories. At the first meeting of the second cycle, the acquisition of teacher activity observation score of 24 with a percentage of 75% in both categories. The second meeting of the second cycle, the acquisition of teacher activity observation score of 28 with a percentage of 87.5% with a good category. Activities of students at the first meeting of the second cycle the number of scores obtained was 23 percentage is 71.87% (Good), while the second meeting of the second cycle he scores the number increased to 30 with a percentage of 93.75% (Very Good).Key words: Cooperative Learning Model Picture And Picture, Learning Outcomes Indonesian